INVOLVEMENT OF SNP MARKER LOCATED ON THE CALCIUM BINDING PROTEIN GENE IN ADAPTIVE TRAITS AND ORGANOLEPTIC PERFORMANCES OF THE OLIVE TREE. - Ben Ayed, R.; Ennouri, K.; Rebai, A. (University of Eloued جامعة الوادي, 2018)
Olive trees importance is mainly due to the economic and health benefits, especially in the Mediterranean basin. Unfortunately, to enhance productivity and quality of olive oil, the study of both molecular and phenotypic characterizations of olive cultivars is crucial. We consider the analysis of 14 Tunisian olive cultivars of known origin sampled from different areas of the country based on SNP marker (CALC) located in calcium binding protein gene. Accordingly, we assessed the potential genotype-phenotypes links between the SNP, on the one hand, and the quantitative and qualitative parameters, on the other. The statistical analysis based on bivariate analysis for the CALC marker suggests that Chemlali varieties with CG genotypes have better capacity to produce fruit, fruit oil, oil content in carotene, cholesterol and linoleic acid than homozygote GG genotypes varieties. These results are confirmed by a multivariate logistic regression.
Article in Journal of Fundamental and sciences. university of el oued
Keywords: Olea europaea L; CALC; calcium binding protein; bivariate analysis; multivariate logistic regression.